Biochemical characterization and activity profiling of recombinant phospholipase A2 from Hemiscorpius lepturus expressed in E. coli with in vivo antibody response - Moslem Najafi; Delavar Shahbazzadeh; Parichehreh Yaghmaie; Hasan Mirzahoseini (Scientific Reports)
Abstract The structure and function of phospholipase A2 (PLA2) in scorpion venom are relatively unexplored, making further study crucial. This research aims to pave the way for a better understanding of scorpion venom, including the biochemical identification and characterization of PLA2 from Iranian Hemiscorpius lepturus, expressed in E. coli, as well as the in vivo study of polyclonal antibodies against PLA2. The PLA2 gene was cloned into pET-26b (+), expressed in E. coli BL21 (DE3) pLysS, and purified by affinity chromatography. The secondary structure of the recombinant protein was analyzed using CD spectroscopy. Biochemical identification included phospholipase activity, temperature, pH, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) methods. New Zealand Albino male rabbits were immunized with 100 µg/ml at 10–12-day intervals using Complete and Incomplete Freund’s Adjuvant. Specific rabbit anti-PLA2 polyclonal antibodies were detected using ELISA. CD spectroscopy analysis revealed the recombinant proteins’ unique composition: 45.1% beta-sheet, 36.6% random coil, 10.3% turn, and 8.1% alpha helix. The highest PLA2 activity was at 250 µg/ml. Phospholipase activity peaked at 25 °C (over 70%) and decreased to about 62% at 37 °C. MIC and MBC tests showed antibacterial and lethal properties at 31.25 µg/ml and 0.5 mg/ml, respectively. This enzymatic protein shows promise as a drug or vaccine candidate against H. lepturus envenomation in future clinical studies.